1948
DOI: 10.1037/h0057028
|View full text |Cite
|
Sign up to set email alerts
|

MMPI correlates of certain movement responses in the group Rorschachs of two college samples.

Abstract: VISUALIZATION of move-JL ment in the Rorschach cards is generally considered to be one of the most psychologically significant of the various types of responses to the test. Rorschach. [6] presented a general interpretation of the determinant of human movement or M which has been accepted to some degree by virtually all later investigators: This component of intelligence can be nothing other than the ability to create new, individual productions, the capacity for "inner creation." In its finest development we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1949
1949
1955
1955

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It was further noted on the scattergrams where the M function was plotted against the criteria of intelligence that a curvilinear relationship seemed definitely to be present. The Eta between M and the Verbal Aptitude [9] proved to be .54, in comparison with the linear r of .37. The Eta for the first administration of the Rorschach in 1947 with the Ohio Psychological Examination proved to be .63.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…It was further noted on the scattergrams where the M function was plotted against the criteria of intelligence that a curvilinear relationship seemed definitely to be present. The Eta between M and the Verbal Aptitude [9] proved to be .54, in comparison with the linear r of .37. The Eta for the first administration of the Rorschach in 1947 with the Ohio Psychological Examination proved to be .63.…”
mentioning
confidence: 73%
“…As has been noted in previous publications [1,3,9], some seventy-five aspects of the Rorschach were quantified 341 and entered on cards for each individual student, thus permitting the usual interquartile item-analysis technique to be employed in the attempt to find correlates of intelligence. Two criteria of intelligence, both admittedly highly verbal, were made use of: (1) for the 1946 group, the Altus' Measure of Verbal Aptitiide; (2) for the 1947 group, the Ohio Psychological Examination, Form, 21.…”
mentioning
confidence: 99%
“…Although a number of research papers have been published treating separately the MMPI and the Rorschach, few comparison studies have been made. Several investigators [1,4,6] have explored relationships between the group forms of the two tests. These studies have not revealed striking association between them.…”
Section: Letterman Army Hospitalmentioning
confidence: 99%